Leukotriene B4 Is a Major Determinant of Leukocyte Recruitment During Otitis Media - Heo, Kyung Wook; Pak, Kwang; Kurabi, Arwa; Ryan, Allen F. (Frontiers in Cellular and Infection Microbiology, 2021)
Background. Pathogens of otitis media (OM) induce inflammatory responses in the middle ear (ME), characterized by mucosal hyperplasia, leukocyte infiltration, and inflammatory mediators, including arachidonic acid metabolites. We studied the role of the eicosanoid leukotriene B4 (LTB4) in OM. Methods. Expression of LTB4-related genes was evaluated by gene array and single-cell RNA-Seq in MEs infected with nontypeable Haemophilus influenzae (NTHi). An inhibitor of LTB4 receptor 1 (i.e. U75302) was also used to block LTB4 responses. Results. ME expression of LTB4-related genes was observed by gene arrays and scRNA-Seq. However, not all genes involved in LTB4 generation occurred in any one specific cell type. Moreover, LTB4 receptor inhibition significantly reduced mucosal hyperplasia and virtually eliminated leukocyte infiltration. Conclusions. ME expression of LTB4-related genes suggest a functional role in OM disease. The fact that LTB4-generation is spread across different cell types is consistent with a transcellular pathway of eicosanoid biosynthesis involving cell-to-cell signaling as well as transfer of biosynthetic intermediates between cells. The dramatic reduction in ME leukocyte infiltration caused by U75302 indicates that LTB4 plays a major role in ME inflammatory cell recruitment, acting via the LTB4R1 receptor. Given that there are many other chemotactic factors that occur in the ME during OM, the ability of LTB4 to activate leukocytes and stimulate their extravasation may explain the effects of inhibition. Reduction in mucosal hyperplasia due to U75302 administration may be secondary to the reduction in leukocytes since LTB4R1 is not expressed by mucosal epithelial or stromal cells. The results suggest that LTB4 receptor antagonists could be useful in treating OM.